Death in the Afternoon - Hemingway, Ernest (London penguin Books, 1966)
Describes all phases of bullfighting, from the raising and training of the bulls to sketches of the bullfighters themselves.
Include Illustrations and Glossary
A description of Spanish bull-fights.
Keywords: Bullfights -- Spain -- Bullfights--Social aspects